Distancia mía: Poemas desde algún viaje - Alliende Luco, Joaquín (Ediciones UC, 2017)
The title of this work reveals the desire of its author, priest and poet, to achieve greater proximity "with each child of God on earth, especially with those whom He has placed closest in our journey", in his words. In the hundred poems compiled here he expresses that feeling and also remembers those people who have been very close to him during his life.